Detection of low intensity auditory evoked responses - GRANDORI, F. (Archives of Acoustics, 1983)
A signal processing technique based on the use of crosscorrelation functions is proposed for the analysis of the auditory evoked brainstem response (ABB). Detection of a response as well as estimation of its position along the time axis (group latency) are shown to be significantly improved after correlation analysis. Results indicate that the method may be applied to systematical investigations of the responses measured – with surface electrodes on the scalp – at extremely low intensity levels.